Designing trans-generational urban communities : an approach towards inclusive cities in the Indian context - Sarkar, Basudatta; Banerji, Haimanti (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"This book examines the inclusiveness of city planning and design to address gaps in policies, strategies and design guidelines for developing trans-generational urban communities in India. Identifying key factors and measurable indicators of trans-generational cities within social, physical, and economic dimensions, the volume highlights the need for establishing age-friendly and child-friendly cities and communities. Through a systematic process of ground data collection, the book explores issues related to health, daily routine, lifestyle, recreation, and socialization within vulnerable groups, considering their physical and cognitive limitations for framing adaptable policies. The volume integrates a bottom-up and top-down approach by integrating the needs and perception of the target group obtained from extensive groundwork with the available theories and literature in allied fields adopting a step-by step synchronized methodology. It also presents the way forward for framing policies focusing on socio-economic security, participation, dignity, care, and self-fulfillment. Offering rich empirical research, this book will be useful for students, teachers and researchers of architecture, urban design, urban geography, urban studies, urban development and planning, and child psychology. It will also be of interest to urban planners and designers, policy planners, local government authorities and professionals engaged in the discipline"--
Introduction- toward a better understanding of vulnerable population in cities, context, issues, challenges and need for inclusion -- Background, theory and development: a critical review of theories, guidelines, norms and planning standards -- Issues and priorities of target groups: a user sensitive approach -- Analysis and synthesis -- A manifesto for change: policies and guidelines for designing trans-generational urban communities and cities (TGUCC) -- Annexures.
Keywords: Community development, Urban -- India; City planning -- India; Intergenerational relations -- India; ARCHITECTURE / General; ARCHITECTURE / Urban & Land Use Planning; SOCIAL SCIENCE / Sociology / Urban